Improving Green IT assessment tool using case-based reasoning concept - Chua, Xiao Ying; Mazlina, Abdul Majid; Lojuntin, Steve Anthony (IOP Publishing, 2020)
In order to know how to measure their level of green practices, green assessment tool is there to act as a guide or as some might called it as a bench marker. Although, there are existing green assessment tools but there is inadequate existing green assessment tool with a recommendation feature. Recommendation feature is meant to aid users especially new user with their green practices. In this paper, case-based reasoning concept is chosen to produce this recommendation features. Besides that, Rapid Application Development Model is used in this research. The expected result of this research is to improve an existing green assessment tool to provide recommendation to user. With this paper, it can help raise user’s level of green awareness and improve their practices.